Agricultural Family School (EFAGO): Social reproduction and peasant culture (Revista Contexto & Educação, 2026)
This article reflects on the relationship between social reproduction and peasant culture, based on the activities of the Goiás Agricultural Family School (EFAGO), considering the life trajectories of its graduates. Historically, peasants have survived by recreating their production system, sometimes with limited technology and sometimes supported by the struggles of social movements and professional associations that have contributed to expanding access and permanence for the peasantry. In this sense, we ask to what extent has the social reproduction of EFAGO graduates been effective, in both its aspects: the world of work outside the family production system and within the family system itself? Methodologically, the article consisted of a qualitative bibliographic study, fieldwork, and interviews to gather information about the relationship with EFAGO graduates. In this movement, we contribute to the political-pedagogical reflection of rural education and influence/collaborate in the analysis of public educational policies for Rural Schools. Finally, "social reproduction" is entirely dependent on the integration of family farming food production systems and the possibility of young people remaining in this activity after studying at EFAS. This is the main point of convergence for work within the family farming system.
Keywords: Rural Education; Pedagogy of Alternation; EFAGO; Graduates and Peasant Culture; Peasant Social Reproduction